Gli studi di teologia di san Josemaría Escrivá / Theological studies of St. Josemaría Escrivá - Francesc Castells i Puig (Studia et Documenta)
Article that covers the different stages of the ecclesiastical studies of St. Josemaría: the initial phase in Logroño, the period of studies at the Pontifical University of Saragossa and his doctoral thesis at the Lateran University. The article analyses particularly the steps preceding his obtaining the doctorate in theology in 1955.